Pengaruh Modal Dan Tingkat Upah Terhadap Nilai Produksi Serta Penyerapan Tenaga Kerja Pada Industri Kerajinan Perak - Ningsih, Ni Made Cahya; Indrajaya, I Gst. Bagus (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112)DO - 10.24843/JEKT.2015.v08.i01.p09, 2015)
Job opportunity is still a major problem for economic development in Indonesia. In order to accelerate economic development, industrialization is one of the government’s strategy. One of them is the silver industry in Sukawati. The purpose of this study are to analyze the direct effect of capital and wage rate to the production value, the direct effect of capital, wage rate, and production value to the labor absorption, and to analyze the indirect effect of capital and wage rate to labor absorption through production value of silver industry in Sukawati, Gianyar. This study is using a Proportional Random Sampling technique with 86 samples. Data were tested using validity and reliability. Furthermore, the data were analyzed using path analysis. The result show that the direct effect of first sub-structural equation is capital has positive and significant impact to production value and wage rate has negative and not significant impact to production value.The result of second sub-structural equation show that capital and production value have positive and significant impact to labor absorption, while wage rate has negative and not significant impact to labor absorption. For the indirect effect, capital has a positive impact to production value and wage rate has a negative impact to production value.
Keywords: labor absorption, production value, wage rate, capital